Lectin-histochemistry: glycogenosis in cattle - Zlotowski, P. (2006)
Ten out of 47 calves that were born in a small Brahman herd from southern Brazil developed progressive muscular weakness and tremors, lethargy and poor body condition. Necropsy was performed on three affected animals. The only gross lesion detected was paleness of the muscles of the trunk and limbs. Multiple cytoplasm vacuoles located in different tissues were the principal microscopic lesions. Vacuoles were particularly evident in skeletal muscles and myocardium. PAS-positive granules were numerous in skeletal muscle fibres and Purkinje fibres of the myocardium, but were also observed in the neurons of the brain and spinal cord, and in the vascular smooth muscle fibres from all the examined tissues. Pretreatment with diastase completely abolished the PAS reactivity. The vacuoles reacted strongly to Griffonia simplicifolia II and Concanavalia ensiformes lectins, whose biding pattern has been reported as useful for demonstration of glycogen. Examination of the electron micrographs revealed that glycogen was free within the cytoplasm or accumulated in membrane-bound granules of several tissues, especially in striated muscle, liver and neurons of the CNS. These findings were consistent with generalized glycogenosis.